Oranges on the Telly: Films and Series in the Christmas Programming of Polish Socialist Television - Klejsa, Konrad; Piepiórka, Michał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
Whilst much has been written about both the organizational structure and particular shows produced and screened by Telewizja Polska (TVP) during the People’s Republic of Poland era, there have been few attempts to investigate this broadcaster’s film programming policy. The article discusses the programming strategies of Polish state television broadcaster TVP in the period 1960–1989. The main focus of the paper is on comparing Christmas schedules with samples of “ordinary weeks” (both: working days and weekends). This proves that the predominance of Western content over productions from Poland and other countries of the Soviet Bloc was typical of Christmas schedules and partially in accordance with the weekend scheme. Furthermore, the article investigates the interference in the television schedule and religious practices. The final section focuses on content analysis of several films most frequently broadcast during Christmas, with a closer look at Polish productions in the final section. The programming policy of Telewizja Polska was to avoid not only Christian content but also movies and tv series which depicted Christmas celebrations in affluent societies. By combining quantitative and qualitative explorations of carefully gathered data on television schedules, the study seeks to propose a new perspective on the history of TVP, thus facilitating future research into other patterns of television programming.